Effect of Combination of Porang and Moringa Flour on Blood Glucose Levels and Body Weight in Rats - Laksmitawati, Dian Ratih; Marwati, Umi; Okta, Fauzia Noprima; Partana, Citra Prastuti (Sciences of Pharmacy, 2024)
Porang tuber is rich in fiber and low in calories of carbohydrates. Moringa oleifera leaf has a high protein and a low content of lipids. Obesity and diabetes mellitus are the risk factors of cardiovascular disease, also known as cardiovascular disease risk factors. Combining of porang and moringa as feed can increase nutrition without causing weight gain. This study aims to determine these two materials as antidiabetic and antiobesity agents. The samples are porang tuber, a combination of porang tuber and M. oleifera leaves, a combination of M. oleifera leaves and wheat flour, wheat flour, and standard feed of mice. The parameters tested in this study are analysis of macronutrients of feed, loss of weight of mice, average consuming feed in 28 days, and reduction of blood glucose with a glucometer. The results obtained are a combination of porang tuber and moringa had a low contain carbohydrates and a high contain lipids and protein, can reduction in body weight of 21%, the lowest consumption of feed, and the lowest fasting and postprandial blood glucose levels compared to the other feeds. A combination of porang and moringa can be an antidiabetic and antiobesity agent.